The Impact Gamification on User Engagement on Shopee (Analysis) - Kelvin, Kelvin; Adnas, Diny Anggraini; Wibowo, Tony (Faculty of Economics dan Business, Atma Jaya Makassar University, 2025)
Shopee, one of the leading e-commerce platforms, has successfully utilized gamification to enhance user engagement and satisfaction. Gamification applies game design elements such as points, leaderboards, and rewards to motivate user interactions and loyalty. This study examines the impact of gamification on user engagement in Shopee through a mixed-method approach, combining quantitative and qualitative data. A structured questionnaire was distributed to 100 active Shopee users, collecting data on user behavior, satisfaction, and the influence of gamification features. Quantitative data were analyzed using SPSS for descriptive statistics, correlation, and regression, while qualitative responses were thematically analyzed. The results reveal that gamification features, particularly rewards and competitions, significantly increase platform visits, user satisfaction, and purchase likelihood. However, personalization and social interaction present opportunities for improvement. This study concludes that gamification enhances user loyalty and engagement, with recommendations for further personalization and interactive features to sustain its effectiveness